Social computing and social media : human behavior : 9th International Conference, SCSM 2017, held as part of HCI International 2017, Vancouver, BC, Canada, July 9-14, 2017, Proceedings.: human behavior : 9th International Conference, SCSM 2017, held as part of HCI International 2017, Vancouver, BC, Canada, July 9-14, 2017, Proceedings. Part I ([2017]) - Unknown
No abstract available